The Synergy of Artificial Intelligence and Cyberpunk Aesthetics in Cinematic Narrative: A Case Study of The Changcuters’ “Karunia Semesta” Music Video - Mahardhika, Satrya (Jurnal Indonesia Sosial Sains, 2025)
This research dives into how Artificial Intelligence (AI) and the cool, edgy look of cyberpunk work together to build stories in movies and music videos. We're using The Changcuters' music video, "Karunia Semesta," as a perfect example. Using a close look at the video and some good old-fashioned research, we first pinpoint all the classic cyberpunk stuff you see: the run-down city vibe (dystopia), the "high tech, low life" contrast, and all those bright neon lights. Then, we explore what AI does in the story it's not just a gadget; it's a stand-in for the problems people face today in our digital world. The music video is short and snappy, making it a powerful way to mix visuals, sound, and big ideas. "Karunia Semesta" is interesting because it mashes up the band's classic rock-and-roll style and retro feel with a dark, AI-focused cyberpunk world and feelings of being alone. This makes us want to dig into why the artists made these choices, viewing AI both as the main topic and maybe even a tool they used to make the video. Ultimately, the goal is to peel back the layers of this story where cyberpunk looks meet AI ideas. By seeing how they work together, we can understand how this connection gives the song's original message a much deeper, more critical meaning.